BIOLOGICAL EFFECTS OF TNF-BINDING VARIOLAVIRUS RECOMBINANT PROTEIN - I. A. Orlovskaya (SPb RAACI, 2014)
Abstract. This review presents a summary of our data concerning in vivo and in vitro effects of recombinant TNF-binding protein from variola virus (VARVCrmB) upon TNF-induced functional changes of human and murine cells. VARV-CrmB protein blocks TNF-induced production of IL-1β and IL-6 by human mononuclear cells, and their in vitro oxidation-related metabolic (OM) activity. VARV-CrmB protein restores TNF-induced reduction of BFU-E+CFU-E colony-forming activity and normalizes TNF-induced effects upon CFU-GM formation in a colony-forming model of human and murine bone morrow cells (BMC). VARV-CrmB protein displays a pronounced in vivo alleviation of LPS-induced endotoxic shock symptoms in SPF BALB/C mice thus significantly increasing survival of experimental animals. Moreover, VARV-CrmBprotein decreases intensity of collagen-induced arthritis at early terms. Application of VARV-CrmB protein results in normalization of TNF-induced increase of migratory and OM activity of murine leukocytes, and exerts corrective effects upon colony-forming ability of murine hematopoietic precursors. Skin application of VARV-CrmB protein decreases leukocyte migration from a skin scrap in afferent phase of DNCB-induced contact reaction, as well as “ear oedema” index. Our results demonstrate TNF-blocking properties of VARVCrmB protein. In summary, our data allow to consider a recombinant variola virus VARV-CrmB as a new potential TNF-antagonist. Its effects can be explained by its ability of neutralizing TNF-induced activation of oxidation-related metabolic, cytokine-producing and migratory functions of effector cells in therapy of pathological inflammatory processes.